The impact of self-efficacy, expectations, and readiness on hearing aid outcomes - Ferguson, Melanie A.; Woolley, Annie; Munro, Kevin J. (Taylor & Francis, 2016)
Objective: To examine the impact of self-efficacy and expectations for hearing aids, and readiness to improve hearing, on hearing aid outcome measures in first-time adult hearing aid users Design: A prospective, single centre design. Predictor variables measured at the hearing assessment included measures of self-efficacy, expectations and readiness to improve hearing. Outcome measures obtained at sixweek follow-up were the Glasgow Hearing Aid Benefit Profile and Satisfaction with Amplification in Daily Life. Study sample: A sample of 30 first-time adult hearing aid users were recruited through a public-sector funded audiology clinic. Results: When measured prior to hearing aid fitting, self-efficacy for hearing aids predicted satisfaction with hearing aids but was not related to other hearing aid outcomes. Expectations of hearing aids, in particular positive expectations, and readiness to improve hearing predicted outcomes for hearing aid satisfaction and benefit, although not hearing aid use. Hearing sensitivity was not correlated with hearing aid outcomes. Conclusions: These results suggest that assessment of expectations of hearing aids, and readiness to improve hearing, may be useful to help identify individuals attending audiology clinics who would most likely benefit from hearing aid provision.